Clinical and cognitive profiles of patients with both Parkinson's disease and essential tremor - GÜNAL, DİLEK (SPRINGER HEIDELBERG, 2013)
Although Parkinson's disease (PD) and essential tremor (ET) are distinct clinical disorders, their coexistence can sometimes cause diagnostic problems. In this study, we conducted detailed investigations of patients with both ET and PD (ET-PD) and compared their clinical and cognitive profiles with those of patients with only ET or only PD. This study examined three groups of patients: the first group had ET-PD concomitantly (n = 9); the second group had only ET (n = 9); the third group had only PD (n = 10). The groups were compared in terms of demographic characteristics, clinical features, and cognitive functions. With the exception of positive family histories, which were more common in ET-PD than in PD patients, we found no differences among the groups with respect to demographic characteristics (p = 0.044). PD-only patients had more akinetic-rigid type Parkinsonism (p = 0.016), and their levodopa response was better than that of ET-PD patients (p = 0.017). Patients with ET-PD obtained significantly lower scores than those with pure ET on several cognitive tests, suggesting a prominent frontal-type cognitive dysfunction. In conclusion ET-PD patients differed from PD patients, showing more frequent familial tremor histories and lower levodopa responsiveness. This patient population also demonstrated more severe cognitive impairments than pure-ET patients. This result suggests that ET-PD patients are a subset of ET patients with more widespread neurodegeneration, which may indicate the presence of a syndrome that includes overlap between ET and PD.
Keywords: Parkinson's disease; Essential tremor; Cognition; Tremor; DYSFUNCTION; DIAGNOSIS; ASSOCIATION; DEMENTIA; DEFICITS; REST